Ventilator-associated pneumonia due to Stenotrophomonas maltophilia: Risk factors and outcome. Issue 3 (March 2020) - Ibn Saied, Wafa; Merceron, Sybille; Schwebel, Carole; Le Monnier, Alban; Oziel, Johana; Garrouste-Orgeas, Maité; Marcotte, Guillaume; Ruckly, Stéphane; Souweine, Bertrand; Darmon, Michael; Bouadma, Lila; de Montmollin, Etienne; et al.
Highlights: SM-VAP occurred lately after the onset of mechanichal ventilation. Exposure to carbapenem and carboxy- or ureido-penicillin during the week before VAP and the severity of disease with respiratory and hematological failures were independent risk factors for the SM-VAP occurrence. The prognosis of patients with SM-VAP was poor and not modified by the adequacy of antimicrobial therapy. Antibiotics exposure the week before VAP and the severity of disease were independent risk factors for the SM-VAP occurrence. Abstract: Background: Stenotrophomonas maltophilia ( SM ) is increasingly identified in intensive care unit (ICU). This study aim to identify risk factors for SM ventilator-associated pneumonia (VAP) and whether it affects ICU mortality Methods: Two nested matched case-control studies were performed based in OUTCOMEREA database. The first episodes of SM -VAP patients were matched with two different control groups: VAP due to other micro-organisms (VAP-other) and Pseudomonas aeruginosa VAP (Pyo-VAP). Matching criteria were the hospital, the SAPS II, and the previous duration of mechanical ventilation (MV). Results: Of the 102 SM -VAP patients (6.2% of all VAP patients), 92 were matched with 375 controls for the SM -VAP/other-VAP matching and 84 with 237 controls for the SM -VAP/ Pyo -VAP matching. SM -VAP risk factors were an exposition to ureido/carboxypenicillin or carbapenem during the week before VAP, and respiratory and coagulation components of SOFA score upper to 2 before VAP. SM -VAP received early adequate therapy in 70 cases (68.6%). Risk factors for Day-30 were age (OR = 1.03; p < 0.01) and Chronic heart failure (OR = 3.15; p  < 0.01). Adequate treatment, either monotherapy or combination of antimicrobials, did not modify mortality. There was no difference in 30-day mortality, but 60-day mortality was higher in patients with SM -VAP compared to Other-VAP ( P  = 0.056). Conclusions: In a large series, independent risk factors for the SM -VAP were ureido/carboxypenicillin or carbapenem exposure the week before VAP, and respiratory and coagulation components of the SOFA score > 2 before VAP. Mortality risk factors of SM-VAP were age and chronic heart failure. Adequate treatment did not improve SM -VAP prognosis. Graphical abstract: Image, graphical abstract